The importance of the foot in life of the people with visual impairment - Tománková, Kristína (Journal of Exceptional People, 2023)
The importance of the foot in the life of the visually impaired is unimaginable. People with visual impairment are a potentially weakened target group regarding the genesis of various orthopedic problems as well as morphological and structural foot deformities. The foot has an important functional relation within the lower limb and body. The paper shows importance of the health state of the foot in their life and describes the foot as an important potential therapeutic tool for maintaining or improving the quality of life. Maintaining a healthy foot in this population should be a significant need. A lot of studies are solving the foot on foot-based interfaces that stimulate the surface of the foot with vibrations. It could be used in several fields such as sensory substitution virtual reality, rehabilitation and among others.